Is a smile important in the eyes of facial aesthetics specialists? (Journal of Face Aesthetics, 2025)
Physiologically, a smile is a facial expression created by the tension of facial muscles, but a smile is the ability to communicate emotions that occurs in all people - this is a psychological approach. We automatically perceive smiling people more friendly, more positively. As can be seen from many reports of the participation of dentists in obtaining a nice smile, who, using modern possibilities of dentistry, influence the creation of a smile. No aesthetic facial medicine procedures will improve the smile except dental aesthetic procedures. The order of procedures is also of great importance - dental treatment should precede other facial aesthetic procedures, which will ensure predictable and long-lasting effects in the field of smile aesthetics.
Keywords: smile; dental aesthetics; aesthetic procedures of various specialties